Pengaruh Strategi Pembelajaran dan Gaya Belajar Terhadap Hasil Belajar Matematika Mahasiswa Manajemen Komputer AMIK Mitra Gama Riau: The Effect of Instructional Strategy and the Learning Style on the Students’ Achievement Mathematics at Computer Management of Amik Mitra Gama in Riau - Novidawaty Tambunan (Universitas Jambi, 2019)
Mathematics learning cannot be separated from the abstract nature of mathematics and the characteristics of the students. Therefore, it is required a teaching strategy that is aligned with student learning styles in order to facilitate achieving maximum learning out comes. This study aims to find out: (1) differences in students’ learning out comes between those were taught with problem-based learning strategies (PBL) and expository learning strategies, (2) differences in students’ mathematics learning outcomes between those who have visual learning styles and kinesthetic learning styles, (3) the interaction between learning strategies and learning styles on mathematics learning outcomes. The results showed that PBL strategy provides higher learning outcomes than expository strategies, kinesthetic learning style provides higher mathematics learning outcomes than visual learning styles, and there is an interaction between learning strategies and learning styles on mathematics learning out comes.